Real-time geospatial surveillance of localized emotional stress responses to COVID-19: A proof of concept analysis. (July 2021) - Edry, Tamar; Maani, Nason; Sykora, Martin; Elayan, Suzanne; Hswen, Yulin; Wolf, Markus; Rinaldi, Fabio; Galea, Sandro; Gruebner, Oliver
Highlights: Tool for real-time monitoring of general emotions and stress as seen in social media. Can detect stress hotspots at the local level over time. Includes a tool to filter out artificial tweets. Application to large anonymized datasets could help inform responses.